Cost-effectiveness of total knee replacement in addition to non-surgical treatment: a 2-year outcome from a randomised trial in secondary care in Denmark. Issue 1 (15th January 2020) - Skou, Søren Thorgaard; Roos, Ewa; Laursen, Mogens; Arendt-Nielsen, Lars; Rasmussen, Sten; Simonsen, Ole; Ibsen, Rikke; Larsen, Arendse T; Kjellberg, Jakob
Abstract : Objective: To assess the 24-month cost-effectiveness of total knee replacement (TKR) plus non-surgical treatment compared with non-surgical treatment with the option of later TKR if needed. Methods: 100 adults with moderate-to-severe knee osteoarthritis found eligible for TKR by an orthopaedic surgeon in secondary care were randomised to TKR plus 12 weeks of supervised non-surgical treatment (exercise, education, diet, insoles and pain medication) or to supervised non-surgical treatment alone. Including quality-adjusted life years (QALYs) data from baseline, 3, 6, 12 and 24 months, effectiveness was measured as change at 24 months. Healthcare costs and transfer payments were derived from national registries. Incremental healthcare costs, and incremental cost-effectiveness ratios (ICERs) were calculated. A probabilistic sensitivity analysis was conducted and the probability of cost-effectiveness was estimated at the 22 665 Euros/QALY threshold defined by the National Institute for Health and Care Excellence. Results: TKR plus non-surgical treatment was more expensive (mean of 23 076 vs 14 514 Euros) but also more effective than non-surgical treatment (mean 24-month improvement in QALY of 0.195 vs 0.056). While cost-effective in the unadjusted scenario (ICER of 18 497 Euros/QALY), TKR plus non-surgical treatment was not cost-effective compared with non-surgical treatment with the option of later TKR if needed in the adjusted (age, sex and baseline values), base-case scenario (ICER of 32 611 Euros/QALY) with a probability of cost-effectiveness of 23.2%. Including deaths, TKR plus non-surgical treatment was still not cost-effective (ICERs of 46 277 to 64 208 Euros/QALY). Conclusions: From a 24-month perspective, TKR plus non-surgical treatment does not appear to be cost-effective compared with non-surgical treatment with the option of later TKR if needed in patients with moderate-to-severe knee osteoarthritis and moderate intensity pain in secondary care in Denmark. Results were sensitive to changes, highlighting the need for further confirmatory research also assessing the long-term cost-effectiveness of TKR. Trial registration number: ClinicalTrials.gov (NCT01410409 ).